Application of the high-pressure water mist system in a railway tunnel rescue station. (1st October 2022) - Bu, Rongwei; Yang, Hongyun; Xie, Ye; Zhao, Wenqiang; Fan, Chuangang; Guo, Zhengwei; Zhou, Yang
Highlights: Full-scale fire suppression experiments and numerical simulations in a rescue station were performed. Suppression effect inside and outside train increased with increasing droplet size. Convective cooling was the main controlling mechanism on suppressing a train fire. Radiation heat flux received by the floor exponentially decayed with the distance from fire. Longitudinal ventilation could effectively improve the suppression effect of water mist system. Abstract: The fire safety of the rescue station as an important issue has not been well concerned. This study investigated the suppression performance of the high-pressure water mist system in a railway tunnel rescue station through CFD (Computational Fluid Dynamics) simulation and full-scale experiments. Eleven groups of numerical simulations and full-scale experiments were designed with various working pressures (5 and 8 MPa), mist droplet diameters (173.2, 178, and 192.9 μm), and longitudinal ventilation velocities (0, 1.5, and 2.5 m/s), in which the simulations were carried out by employing SIMTEC (Simulation of Thermal Engineering Complex) software. Results show that the temperature control effect both in the carriage and above the platform increases along with a bigger mist droplet diameter, in which convective cooling is found to be the main controlling mechanism. However, with increasing mist droplet diameter, smoke concentration increases, and oxygen concentration decreases. Moreover, the radiant heat flux received by the floor presents an increasing first and then decreasing tendency with the increase of distance away from the fire source (denoted by l ). Furthermore, in the region of l ≥ 2.5 m, radiant heat flux has an exponential attenuation with l . In addition, it is also found that the longitudinal ventilation system can effectively improve the suppression performance of the water mist system on a shielded fire. With increasing ventilation velocity, smoke temperature and radiant heat flux in the region of l ≥ 2.5 m decrease. In all cases, numerical results match well with experimental results, which validates the effectiveness of the CFD simulation. This study provides a significant reference for the fire safety design of the railway tunnel rescue station.